Anti-interleukin (IL)-5 as a steroid-sparing agent in chronic eosinophilic pneumonia. (2nd January 2020) - Sarkis, Edmond; Patel, Sumit; Burns, Kenneth; Batarseh, Hanan; Mador, M. Jeffery
Abstract: Introduction : Anti-interleukin (IL)-5 therapy is a novel drug class clinically effective in patients with diverse eosinophil-related disorders such as allergic eosinophilic asthma, eosinophilic granulomatosis with polyangiitis (EGPA), nasal polyposis, eosinophilic COPD, and other non-pulmonary disorders such as eosinophilic esophagitis. Chronic eosinophilic pneumonia (CEP) is a steroid responsive disorder, however, relapses are common following corticosteroid tapering. Case Study : We present the case of a 42-year-old woman with steroid-dependent relapsing CEP successfully treated with anti-IL-5 antibody. Results : Treatment with anti-IL-5 antibody resulted in remission with the ability to taper off the steroids, and no recurrence of the disease for 6 months. Conclusion : Our case report supports the potential use of anti-IL-5 therapy for remission of patients with CEP with recurrent relapses. Whether, it would also be an effective initial therapy might also be an area that deserves future investigation.